Strengthening Local Governance of Secondary Forest in Peru - Sears, R.R.; Guariguata, Manuel R.; Cronkleton, P.; Miranda Beas, C. (MDPI, 2021)
Natural forest regrowth is critical for restoring ecosystem services in degraded landscapes and providing forest resources. Those who control tenure and access rights to these secondary forest areas determine who benefits from economically charged off-farm opportunities such as finance for forest restoration, selling carbon credits, and receiving payment for ecosystem services. We explore multiple dimensions of secondary forest governance in Peru, where the lack of official government statistics of the extent, geography, and ownership, coupled with low state capacity, prevents the development of governance structures that could stimulate their sustainable management. In this paper, we review the challenges to secondary forest governance, and the opportunities to strengthen it, focusing on beneficial outcomes for smallholder farmers. We characterize secondary forest types, extent, and persistence in Peru, followed by a presentation of the social dimensions of their governance. We identify four entry points for government to take action: national mapping of the socio-geography of second growth forest, regularize the property rights of untitled landholders, relax forest regulations, and provide incentives, not sanctions, for secondary forest management. Overall, we recommend folding secondary forest governance into a landscape approach. In Peru, strengthening local forest governance could help to drive benefits of climate change mitigation incentives directly to local forest stewards.